2019
DOI: 10.1371/journal.pone.0213515
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and spatial characterization of the red fox (Vulpes vulpes) population in the area stretching between the Eastern and Dinaric Alps and its relationship with rabies and canine distemper dynamics

Abstract: Information on the population dynamics of a reservoir species have been increasingly adopted to understand and eventually predict the dispersal patterns of infectious diseases throughout an area. Although potentially relevant, to date there are no studies which have investigated the genetic structure of the red fox population in relation to infectious disease dynamics. Therefore, we genetically and spatially characterised the red fox population in the area stretching between the Eastern and Dinaric Alps, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 79 publications
(109 reference statements)
1
15
0
Order By: Relevance
“…The exact role of foxes in the epidemiology of certain RVA genotypes is currently unknown; however, a rising presence of foxes in urban and semi-urban settings may pose as a risk for disease spillover among humans and animals [12]. Our results indicate a possible role of foxes as RVA reservoirs of a broad range of genotypes usually considered typical of domestic animals and humans.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The exact role of foxes in the epidemiology of certain RVA genotypes is currently unknown; however, a rising presence of foxes in urban and semi-urban settings may pose as a risk for disease spillover among humans and animals [12]. Our results indicate a possible role of foxes as RVA reservoirs of a broad range of genotypes usually considered typical of domestic animals and humans.…”
Section: Discussionmentioning
confidence: 71%
“…Among wild animals, red foxes (Vulpes vulpes) are especially interesting since they colonize urban and semi-urban areas and, therefore, may represent a disease spillover risk to human and animal health [12]. So far, the research on RVAs in red foxes comes down to one result obtained by negative-contrast electron microscopy [13] and the recent description of RVA as a causative agent of encephalitis [14].…”
Section: Introductionmentioning
confidence: 99%
“…[69]). Influencing factors may include variations in host population density, host population dynamics, social, behavioural and spatial ecology (including dispersal, migration and changes in home range sizes), as well as by various other factors including landscape structure, environmental and climatic factors, host(s) life history, and host and pathogen genetic diversity [11, 7074]. It can be hypothesised that the described epidemiological transitions may have been eased by three successive processes.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious diseases such as sarcoptic mange [7, 63, 92], canine distemper [9395] and rabies [76] can drive wild canid population dynamics by altering population size, growth rate, animal distribution, migration patterns and genetic diversity [9698]. Studies on interactions between diseases [99, 100] in wildlife are rare, but comparable interactions between distemper and sarcoptic mange were hypothesized in wolves ( Canis lupus ) in the USA [95] and in Spain [101], while an association between genetic structure of fox population and infection with distemper and rabies was observed in Northern Italy [70]. This study suggests that rabies-related changes in the fox population dynamics affected the dynamics of sarcoptic mange, a phenomenon that has also recently been observed in Estonia [102104].…”
Section: Discussionmentioning
confidence: 99%
“…Goldsmith et al [37] also found evidence of fine-scale geographically isolated genetic clusters, but the levels of admixture among these clusters undermined correlations of the host genetic structure of red fox with AR strains. These findings were not surprising given red fox are widely dispersed carnivores, native to much of the northern hemisphere as a matter of their high dispersal capabilities, their generalist nature, the capacity of the species to exhibit a phenotypic plasticity in response to changes in selective pressures, and historical red fox translocations [42][43][44][45][46][47]. The lack of correlation of AR strains with low levels of red fox population genetic structure, may also be related to observations that red fox have expanded their distribution northward, coinciding with Arctic warming, a factor postulated to continue to influence and alter AR dynamics [37,[48][49][50].…”
Section: Introductionmentioning
confidence: 99%